The Influence of Nutrient Solution Concentration in the Fertigation System on Tomato Plant Growth in Bengaluru, India: Pengaruh Konsentrasi Larutan Nutrisi dalam Sistem Fertigasi terhadap Pertumbuhan Tanaman Tomat di Bengaluru, India - JattLife (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This study aims to investigate the influence of nutrient solution concentration in the fertigation system on tomato plant growth (Solanum lycopersicum) in Bengaluru, India. Bengaluru is an important agricultural center in the country; however, plant growth is often hindered by land limitations, water resources, and climate fluctuations. Therefore, this research seeks an efficient and effective solution by implementing fertigation systems to enhance agricultural yields in the region. The study employs an experimental design with a randomized complete block approach and is conducted in Bengaluru, India. Tomato plants are grown in homogeneous groups, and each group serves as one experimental block. The nutrient solution concentration in the fertigation system is set at different treatment groups, including low, medium, and high concentrations, along with one control group without additional nutrient application. The results of the study indicate that the nutrient solution concentration in the fertigation system significantly impacts tomato plant growth in Bengaluru. Treatment groups with higher nutrient concentrations demonstrate improved vegetative and generative growth, with increased plant height, leaf quantity, and size, as well as higher harvest yields. Additionally, fruit quality, including sugar and vitamin content, also increases in treatment groups with the appropriate nutrient concentration.